READING MASCULINITY ON 9GAG - Veronica Veronica; Priska Febrinia Handoyo (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
This study is conducted to reveal the masculine qualities stereotyped on 9GAG by 9GAG users. There are two main theories used in analyzing this study, gender stereotype and denotation & connotation. (). First, the gender stereotype concepts used are from Brannon (2004) and Wood (2008). The first part of the study discusses 9GAG popular posts which content subtly contains of Alpha Male qualities. The result is the users show preferences on conventional masculine qualities. The second part of the study discusses 9GAG popular posts which content subtly contains of Beta Male qualities. The result is there are some specific feminine or Beta Male sides 9GAG users accept in men. In conclusion, 9GAG users still focus more on masculine qualities, especially masculine physical features, in men. Feminine qualities in men can be accepted by the community if men possess the conventional masculine physical features first.